2009
DOI: 10.1128/mcb.01319-08
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint-Dependent Regulation of Origin Firing and Replication Fork Movement in Response to DNA Damage in Fission Yeast

Abstract: To elucidate the checkpoint mechanism responsible for slowing passage through S phase when fission yeast cells are treated with the DNA-damaging agent methyl methanesulfonate (MMS), we carried out two-dimensional gel analyses of replication intermediates in cells synchronized by cdc10 block (in G 1 ) followed by release into synchronous S phase. The results indicated that under these conditions early-firing centromeric origins were partially delayed but late-firing telomeric origins were not delayed. Replicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…DNA lesions themselves slow polymerase progression, but in budding yeast this effect was found to be independent of Mec1 and Rad53 122 . The CHK1 homolog in fission yeast, Cds1, was suggested to slow fork movement in response to DNA damage 139 . Similarly, in human cells CHK1 was shown to slow fork elongation rates following camptothecin-induced DNA damage 140,141 .…”
Section: Atr Functions During Dna Replicationmentioning
confidence: 99%
“…DNA lesions themselves slow polymerase progression, but in budding yeast this effect was found to be independent of Mec1 and Rad53 122 . The CHK1 homolog in fission yeast, Cds1, was suggested to slow fork movement in response to DNA damage 139 . Similarly, in human cells CHK1 was shown to slow fork elongation rates following camptothecin-induced DNA damage 140,141 .…”
Section: Atr Functions During Dna Replicationmentioning
confidence: 99%
“…However, our results do not overrule the idea that inhibition of the origin firing near the forks also inhibits fork restart in WRN-WT cells in response to CPT, which warrants further study. Importantly, Kumar and colleagues recently showed the persistence of replication intermediates in MMS-treated fission yeast by using 2D-gel analysis of replication intermediates (Kumar et al, 2009). This suggests the inhibition of fork progress in response to MMS.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro study with Xenopus egg extracts indicated that the DNA damage checkpoint response induced by MMS was closely correlated with the process of DNA replication, mainly involved in the double-strand breaks in replication forks [28] . The study in S. pombe revealed that the MMS treatment induced S-phase delay through the inhibition of both origin firing and replication fork movements [29] . In the present studies, Comet assay was applied to detect DNA damage in MMS-treated HeLa cells, which showed that the MMS treatment caused DNA strand breaks in HeLa cells (unpublished data; and see ref.…”
Section: Discussionmentioning
confidence: 99%